LEGAL PROTECTION FOR HOUSED WORKERS DURING THE COVID-19 PANDEMIC IN CIREBON CITY - Irma Maulida; Agus Dimyati; Dessy Ika Putri (JILPR Journal Indonesia Law and Policy Review, 2022)
The Covid-19 pandemic which is also endemic in the city of Cirebon has caused enormous losses in various sectors. The company gave the reason that this happened because of the Force Majuere effect of the Covid-19 pandemic. In the end, they were laid off only with a certificate obtained from the hotel without any clarity from the company in the letter when they would return to work, and the rights they obtained. In this study, the author uses a normative juridical approach, namely the approach method through the applicable legislation and is used as prime legal material data. Then proceed with the collection of secondary legal material data obtained from literature studies in the form of law books, legal journals, and other literacy related to the core of this research. As well as tertiary legal materials obtained from legal dictionaries, Indonesian dictionaries, and other dictionaries. The results of the study using the above method indicate that: (1) There is an employment relationship, workers who are laid off are still entitled to a complete certificate containing how long they have been laid off, the amount of wages received, the rights obtained must be listed in accordance with there is an element of a written agreement for legal certainty, (2) laid-off workers are still entitled to their full rights because the company experiencing the impact is included in the category of relative force majeure. Then the company can apply for a wage deferral.